DICOM: A Revolution in Facet of Maxillofacial Imaging - Samadrita Paul; Balaji Pachipulusu; TS MAHESH Kumar; Poornima Chandra (Journal of Clinical and Diagnostic Research, 2024)
Digital Imaging and Communications in Medicine (DICOM) is a paradigm that enables interoperability between health-related digital applications, imaging devices, and Picture Archiving and Communications Systems (PACS). DICOM has its foundation in the USA, established by the American College of Radiology (ACR) and the National Electrical Manufacturers Association (NEMA) in 1983 with the objective of establishing a “gold standard” for monitor and print-copy devices. In 1996, the American Dental Association (ADA) became a member of DICOM, followed by the American Academy of Oral and Maxillofacial Radiology and the American Association of Orthodontics. A working committee specifically for dentistry (WG-22) was initiated in 2003, and in 2005, it was finally adopted as an international standard. Currently, it is internationally recognised as the standard configuration for compatibility between dental radiological images and various scanners and digital X-ray devices. DICOM synchronises network communication and facilitates the exchange of patient data through a transmission protocol. The purpose of the present paper is to emphasise the reliance of digital dentistry on DICOM and its relationship with Three-Dimensional (3D) printing.